The Influence of the privacy concern and social advertising type on the attitude and behavior - Wang, Chih-Chien; Yang, Yolande Yunhsiou; Lin, Ming-Ru (International Journal of Informatics and Information Systems, 2019)
Nowadays social media can collect consumers' online behavior. The enterprises make the customized advertisement to achieve targeting marketing and close consumers' needs. With the right of privacy, the consumers pay attention to this kind of advertisement. In this study, we made the online questionnaire. Asking the privacy concern, and analyzing the advertising attitude and behavior in a different advertising situation. The result we found that customized advertising made consumers increase positive attitude, but made negative attitude on advertising behavior like click, share, etc. In addition, both male and female have different responses to customized advertisements and intimate products advertisements. The result can serve a reference for manufacturers to make advertising strategies in the future.